Facile Control of Structured ZnO Polymeric Nanoparticles through Miniemulsion Polymerization: Kinetic and UV Shielding Effects - Narissara Sudjaipraparat; Teeraporn Suteewong; Pramuan Tangboriboonrat (Polymers, 2021)
Zinc oxide polymeric nanoparticles (ZPPs) of poly (styrene-co-acrylic acid) P(St/AA), containing oleic acid modified zinc oxide nanoparticles (OA-ZnO NPs), were synthesized via miniemulsion polymerization. By simply adjusting the quantity of reactants, i.e., sodium dodecyl sulfate (SDS) surfactant, potassium persulfate (KPS) initiator, and divinyl benzene (DVB) crosslinking agent, the location of ZnO NPs were altered from the inner (core) to the outer (shell), leading to core-shell and Pickering-like morphologies, respectively. The Pickering-like ZPPs were obtained when using SDS at below or equal to the critical micelle concentration (CMC). At above the CMC, the complete encapsulation of OA-ZnO NPs within the ZPPs depicted a kinetically controlled morphology. The transition to Pickering-like ZPPs also occurred when reducing the KPS from 2 to 0.5-1%. Whereas the DVB accelerated the polymerization rate and viscosity in the growing monomer-swollen nanodroplets and, hence, contributed to kinetic parameters on particle morphology, i.e., an increase in the DVB content increased the rate of polymerization. A hollow structure was obtained by replacing styrene with the more hydrophilic monomer, i.e., methyl methacrylate. All ZPPs-incorporated poly (vinyl alcohol) (PVA) films greatly improved shielding performance over the UV region and were relatively transparent on a white paper background. Due to the large number of ZnO NPs in the central region and, hence, the ease of electron transfer, composite films containing core-shell ZPPs possessed the highest UV blocking ability. ZnO NPs in the outer part of the hollow and Pickering-like ZPPs, on the other hand, facilitated the multiple light scattering according to the difference of refractive indices between the inorganic shell and organic/air core. These results confirm the advantage of structured ZPPs and their potential use as transparent UV shielding fillers.
Keywords: Advanced Polymer Synthesis and Characterization; Polymer composites and self-healing; Surface Modification and Superhydrophobicity